EP1302 Video endoscopic inguinal lymphadenectomy using 3D scope with sparing saphenous vein. (1st November 2019) - Park, JS; Lee, SH
Abstract : Introduction/Background: Inguinal lymphadenectomy is necessary when FIGO stage IB or higher. However, conventional inguinal lymphadenectomy has a high morbidity. Video endoscopic inguinal lymphadenectomy(VEIL) is emerging as a minimally invasive treatment to reduce postoperative complications. We report the case of the first VEIL using 3D scope performed in a patient with early stage vulvar carcinoma. Methodology: 62 years-old woman visited for right vulvar area pain. The excisional biopsy was done and pathologic diagnosis was squamous cell carcinoma. Preop imaging study revealed Ill-defined hypermetabolic activity in right inguinal area on PET-CT and a 1.2 cm hypointense lymph node in right inguinal area on MRI(T2WI). Modified right radical hemivulvectomy, coverage with V-Y advancement flap, right inguinal lymphadenectomy, Video-endoscopic guided left inguinal lymphadenectomy was planned. VEIL was not available on right side due to flap surgery. Surface marking for femoral triangle was made on the skin. Three ports were used. Balloon trocar was used for avoid leakage of carbon dioxide gas. The main landmarks of dissection were medially the adductor longus muscle, laterally the sartorius muscle, superiorly the inguinal ligament and the inferior margin was the apex of the femoral triangle. After identified the saphenous vein, we preserved it to reduce the risk of lymphedema. Several lymph nodes were obtained. At the end of the surgery, a drain was inserted through the port. Results: The total operation time was 335 minutes and left VEIL took 54 minutes. The total number of nodes removed was 8. The pathologic diagnosis was invasive squamous cell carcinoma. moderately differentiated(stage IB). There is no metastasis on any lymph node. Drain was removed on the 15th postoperative day. Hospital stay after operation was 18 days. No postoperative complication was noted. Conclusion: Use of 3D scope in VEIL may provide a less invasive approach and aid surgeons by enhancing vision enabling saphenous vein-sparing technique. Disclosure: Nothing to disclose